Research and innovation missions to transform future water systems - Smith, Mark; Gordon, C.; Kittikhoun, A.; Molwantwa, J.; Mollinedo, P. P.; Romdhane, A. B.; Shrestha, R.; Tindimugay, C.; McDonnell, Rachael (Springer, 2023)
The United Nation 2023 Water Conference offers a critical opportunity to catalyse actions and innovations that bring increased water security to vulnerable communities across the globe. Researchers have an important role in supporting the delivery of needed on-the-ground impact, but their work must be informed by the priorities and necessities of Global South implementors.